2021
DOI: 10.1038/s41598-021-00520-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and characteristics of silver nanoparticles biosynthesized from Carduus crispus

Abstract: In recent years’ synthesis of metal nanoparticle using plants has been extensively studied and recognized as a non-toxic and efficient method applicable in biomedical field. The aim of this study is to investigate the role of different parts of medical plant Carduus crispus on synthesizing silver nanoparticles and characterize the produced nanoparticle. Our study showed that silver nanoparticles (AgNP) synthesized via whole plant extract exhibited a blue shift in absorption spectra with increased optical densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 44 publications
9
71
1
1
Order By: Relevance
“…These phytocompounds may play a role in stabilizing the particle size of the prepared silver metals within the nanoparticle ranges. Similar FT-IR results were reported in previous studies of green synthesized AgNPs 16 , 31 , 32 . The chemical AgNPs FT-IR spectrum peaks were corresponding to the O–H stretching/N–H stretching of an amine group and C=O groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These phytocompounds may play a role in stabilizing the particle size of the prepared silver metals within the nanoparticle ranges. Similar FT-IR results were reported in previous studies of green synthesized AgNPs 16 , 31 , 32 . The chemical AgNPs FT-IR spectrum peaks were corresponding to the O–H stretching/N–H stretching of an amine group and C=O groups.…”
Section: Discussionsupporting
confidence: 90%
“…The crystalline nature of AgNPs exhibited the FCC crystal nature of metallic silver as (111), (200), (220), and (311) plane lattice observed in the XRD pattern of ginger and chemical AgNPs and (111), (200), and (311) plane lattice in XRD pattern of cinnamon AgNPs. Similar XRD pattern was observed in previous studies of green synthesized AgNPs 32 , 35 .…”
Section: Discussionsupporting
confidence: 88%
“…So, it is difficult to enter into gram-positive bacteria than gram-negative bacteria ( Erjaee et al, 2017 ). Earlier studies have shown that AgNPs were active against a wide range of pathogenic bacteria due to their effective antibacterial properties ( Gandhi et al, 2021 , Skóra et al, 2021 , Urnukhsaikhan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that our AgNPs showed greater activity against the Gram-negative (E. coli and K. pneumoniae) than Gram-positive (E. faecalis and S. aureus) bacteria. Urnukhsaikhan et al [54] reported contradictory results in which the AgNPs synthesized from the aqueous extracts of Carduus crispus collected from Mongolia exhibited higher potency against Gram-positive bacteria Micrococcus luteus (ZOI = 7 ± 0:4 mm to 7:7 ± 0:5 mm) in comparison to the Gram-negative E. coli (ZOI = 5:5 ± 0:2 mm to 6:5 ± 0:3 mm). They had concluded that the antibacterial activity of different plant-based AgNPs does not depend on the thickness and texture of the bacterial cell wall only.…”
Section: 4mentioning
confidence: 99%